Application of Eggshell Powder as an Additive Cement on Increasing the Compressive Strength of Papercrete - Muklis, Muhammad; Safarizki, Hendramawat; Budianto, Wibowo (Universitas Ibn Khaldun Bogor, 2026)
Papercrete is a lightweight concrete variant primarily composed of paper, which is characterized by its low compressive strength. This study aims to enhance the compressive strength of papercrete through the incorporation of eggshell powder (ESP) as a partial cement replacement. Given the significant volume of eggshell waste generated in households, this research explores its potential as a sustainable additive in concrete formulation. The experimental design involved the preparation of control concrete mixtures without ESP, incorporating 2.5% and 5% paper by weight of sand. Additionally, concrete mixtures with ESP were formulated at 5% and 7% by weight. A total of 35 cylindrical specimens (15 cm x 30 cm) were cast for testing. Compressive strength evaluations were conducted at 7 days of curing. The findings indicate that the addition of eggshell powder significantly improves the compressive strength of papercrete, with an optimal enhancement observed at a 5% ESP substitution level, yielding a compressive strength of 9.06 MPa in conjunction with a 2.5% paper mix.